AN ANALYSIS OF READING EXERCISES IN THE SEVENTH GRADE OF THE BRIGHT BOOK FOR JUNIOR HIGH SCHOOL, PUBLISHED BY ERLANGGA FOR KURIKULUM MERDEKA IN 2022 - Parel, M. Ewaldo; Puspita, Hilda; Lubis, Azhar Aziz (UNIB Press, 2025)
This research aims to find out the composition and distribution of Higher Order Thinking Skill (HOTS) in the “Bright” an English Textbook for Grade Seven junior high school. This research used a descriptive quantitative method. The data were obtained through analysis of every reading exercises that follow essay question, based on Revised Bloom’s Taxonomy. The instrument used is an analysis card and checklist table, the researcher collects and lists all of the reading exercises in a bright book, then separates all the reading exercises based on chapters. HOTS contained in the table form identified by the researcher. Analysis cards become guidelines to make questions into a well-balanced portion of HOTS capacity. Keywords utilized to identify the question to which it belongs either LOTS or HOTS in table form. The result showed that the composition of HOTS presented in the reading exercises is only 12% consisting of Analyze 7%, Evaluate 3%, and Create 2%, lower than LOTS which take almost half of the book take 88% with Remember (C1) the most dominant. As result shows, it is not enough if the teacher just only uses the English textbook as a teaching tool to improve students' HOTS ability.